(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Polycystic ovary syndrome (PCOS) is a complex endocrine disorder prevalent among women of reproductive age. Solanum nigrum leaf is used traditionally in the treatment of various gynecological disorders. The toxicological effects of aqueous extract of Solanum nigrum leaves (AESNL) at 200 mg/kg body weight on anastrozole-induced in polycystic ovarian syndrome was investigated in female Wistar rats. Sixteen female Wistar rats (190.56 ± 5.35g) were assigned into 4 groups (A - D) of four animals each: animals in group A received 0.5 ml of distilled water orally on daily basis for 14 days while the anastrozole-induced rats in groups B, C, and D also received orally 0.5 ml of distilled water, 7.14mg/kg of metformin (reference drug) and same volume of the extract corresponding to 200 mg/kg body weight of AESNL respectively. Parameters assayed for were liver function tests, kidney function tests and enzyme assays. The result obtained revealed that AESNL mitigated anastrozole-treatment related increases in albumin, uric acid, total protein parameters, total bilirubin, liver and serum aspartate aminotransferase, kidney alkaline phosphatase, liver gamma-glutamyl transferase activities, and aggravated the increases in urea, direct bilirubin, creatinine, liver and serum alkaline phosphatase, and serum gamma-glutamyl transferase activities. Therefore, the aqueous extract of Solanum nigrum leaves at the 200 mg/kg body weight might not be completely safe when used in the treatment of PCOS due to alterations in toxicological parameters evaluated in this study.